Management of divergent production network using decentralised multi-level capacitated lot-sizing models. (2016) - Zoghlami, Nesrine; Taghipour, Atour; Merlo, Christophe; Abed, Mourad
Coordination between manufacturing organisations plays an important and an essential role in performance improvement of all members of supply networks. To achieve a coordinated plan, information sharing is considered as an essential tool, which facilitates the coordination of operations planning. In the real world, sharing the strategic information can be considered as a risk for independent organisations. So many autonomous organisations do not prefer to exchange this information to their partners but the main question is how the coordination can be achieved without these information. This paper seeks to demonstrate how an incentive system can be used and can affect the problem of supply network operations planning coordination when the organisations do not prefer to exchange the strategic information. Our work presents a general approach in order to manage a divergent supply network. Our objective is to show that network coordination of plans can be achieved without exchange of strategic information.